PENGEMBANGAN SISTEM INFORMASI RETENSI REKAM MEDIS DI RUMAH SAKIT DUSTIRA CIMAHI - Taryanto, Ardi; Nur Handayani, Lilis (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
This study aimed to develop a medical record retention information system with a case study at Dustira Cimahi Hospital. The data collection techniques used were by observations and completed by literature study which had related with the problems. Software development methods was made using waterfull. From the research conducted, it was found several problems associated with the retention information system which has running, such as: the implementation of retention was done directly with sorting out medical record file without the computer, the absence of a retention schedule medical record file, there is no storage space inactive and off medical record file. Therefore it is necessary to develop a medical record retention information system in the form of an application implemented with the Microsoft Visual Basic.Net 2010 programming language and the Database Access System / DBMS Microsoft Access. So that this application is expected to help hospitals in overcoming file retention problems and data retention processing can be better in the future.